IMPLEMENTASI MAJALAH DIGITAL SEKOLAH BERBASIS WEBSITE UNTUK MENINGKATKAN LITERASI SISWA SMPN 6 TANGERANG SELATAN - Aidil Amal; Kresna Surya Herlambang; Muhamad Fatir Fahreji; Naufal Nur Dzaky; Rendy Ferdiansyah; Rifqi Khumaidi; Rona Nurheni Nadapdap; Vanessa aprillia Diaz; Vebronia Bikolo; Vivi Veronica; Herwis Gultom (Abdi Jurnal Publikasi, 2026)
Students’ literacy skills are fundamental competencies that support learning activities at the junior high school level. However, low reading interest and limited writing skills remain common challenges in many schools. This study aims to implement a website-based school digital magazine as a literacy medium and analyze its impact on improving students’ literacy. A descriptive approach was employed, with data collected through observation, questionnaires, and documentation. The digital magazine was implemented through the school website as a platform for publishing students’ works and providing digital reading materials. The results indicate that the website-based digital magazine increases students’ engagement in reading and writing activities and receives positive responses toward school literacy programs. Therefore, a website-based digital magazine can be considered a relevant and practical alternative literacy medium for junior high schools.